Botulinum toxin in the treatment of sialorrhea - Svetel Marina; Vasić Milan; Dragašević Nataša; Pekmezović Tatjana; Petrović Igor; Kostić Vladimir S. (Vojnosanitetski Pregled)
Background/Aim. Botulinum toxin-A (BTX-A) is known to block the release of acetylcholine from motor and autonomic nerve terminals and may significantly decrease saliva production when injected intraglandulary. The aim of this study was to evaluate effects of BTX-A injections in the treatment of disabling sialorrhea in various neurological disorders. Methods. This study included 19 consecutive patients with significant sialorrhea associated with various neurological disorders. Out of them 13 patients were with Parkinson's disease, two with pantothenate kinase-associated neurodegeneration, two with multiple system atrophy, one with Wilson's disease, and one patient with postoperative sialorrhea. Botulinum toxin-A (Dysport®, Ipsen Pharma) was injected into the parotid glands with (n = 7 patients) or without (n = 12 patients) ultrasound guidance. All the patients were scored before and after the treatment and in weekly intervals thereafter using the salivation item of the part II (Activities of Daily Living) of the Unified Parkinson's Disease Rating Scale (UPDRS). Results. Thirteen patients (68%) reported beneficial effect of BTX-A injection, while 6 of them (32%) had no response at all. The sialorrhea scores before and after the treatment were 3.1 ± 0.1 (range 2-4) and 1.8 ± 0.1 (range 0- 3), respectively (t = 5.636; p < 0.001). There was no difference in the magnitude of response between the groups with (t = 4.500; p = 0.004) and without (t = 3.674; p = 0.005) ultrasound control of injection sites. Adverse effects were registered in 5 patients (26%). Conclusions. Botulinum toxin-A injections to easily accessible parotid glands, without necessity for ultrasound guidance, are safe and efficaceous treatment for sialorrhea in different neurological disorders.